Educa????o e arte: as crian??as de Portinari - Lima, Karla Eleut??ria Cavalcanti Silva de (2016)
The present research work has analyzed and discussed the works of art with images of children from Candido Portinari and his political participation through art. His artistic production constituted our study object, by which we aimed to answer the following questions: How many Portinari artworks have images of children? On which year and decade did he most produced? Which topics were covered? What is the relation between these images and the education of the time? Since he painted children, is it possible to say that Portinari was an educator? Why? This study has collected data from bibliographic and field research, using primary and secondary sources. We analyzed the children role in the world: its??? presence on art, education and social means; then we followed this same track through Brazil; and finally, we got to the life of this artist, presented by means of a historical contextualization of the political and educational scenery, from the First Republic to the end of the New Republic. His artistic production was studied from ten works: Maria Jord??o Arruda e sua filha (1926), Arthur Bernardes de Souza Filho (1960), Cabe??a de crian??a (1955), Nossa Senhora do Carmo (1944), Crian??as brincando no p??tio da escola (1933), Grupo de alunos (1945), Despejados (1934), Mulher ajoelhada com filho morto (1955), Festa em Brodowski (1933) e Menino dormindo (1960). A study of the contradictions and possibilities of the presence of children on Portinari???s work was carried out, highlighting the following analysis issues: 1st: the professional identity of the artist; 2nd: his political engagement; 3rd: his conscience of class; 4th: His freedom of creation. Finally, we sought to answer if Portinari is an educator and why. We proved our research hypothesis: Portinari regarded children better than national development policy???s educational system ideologies. He proved that by his political, technical, and especially artistic compromise. For that, he is an educator.